Electricity sector data for policy-relevant modeling: Data documentation and applications to the German and European electricity markets - Jonas Egerer; Clemens Gerbaulet; Richard Ihlenburg; Friedrich Kunz; Benjamin Reinhard; Christian von Hirschhausen; Alexander Weber; Jens Weibezahn (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
[Summary] The dataset for the European electricity system needs a variety of data to cover the relevant characteristics of the industry. The more general data on aggregated generation capacities, historic generation, and consumption can be found with a consistent data specification for most European countries in databases like EUROSTAT. On the other hand, more detailed data like generation capacities for conventional and renewable sources are usually not publicly available, sometimes not even on a national basis, and henceforth appropriate assumptions or commercial databases are required to retrieve the necessary information. Due to the already mentioned issue with regard to available information, setting up a consistent dataset for the European electricity system is more difficult in comparison to the German electricity system, where mostly consistent data is publicly available. Similar projects on a European level could be helpful for a consistent dataset. Having set up a dataset for Europe, the model application shows that the general tendencies on regional generation and import/export pattern can be captured. However, differences are obvious in particular regions where the model shows different results than the historic values which may be based either on the rough modeling approach or on an insufficient data supply. To that end, the presented dataset and model application are a continuous process, and further steps are required to improve the data quality as well as the modeling. Among others, the implementation of cogeneration restrictions, improvement of renewable generation and their distribution, and an intertemporal model calibration are potential improvements for the future.
Keywords: 330